2020
DOI: 10.1111/ciso.12355
|View full text |Cite
|
Sign up to set email alerts
|

Karachi & COVID‐19: Testing, Kinship & illness

Abstract: In the past decades Karachi, the largest city of Pakistan, has experienced massive demographic transformations. The inflow of migrants during the rapid industrialization in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…2 In some cases, I observed that families did get tested when there was suspicion because of infection, especially after a death in the family. As I show in another article, one woman in Nazimabad (Karachi) had gotten herself tested when her husband died of typhoid and was being treated with suspicion by her neighbours (Khan 2020). Recent literature has made contributions about the reliability of knowledge about COVID-19 symptoms and prevention in low-income settings (Austrian et al 2020;Lau et al 2020).…”
Section: Imagining the Disease-free Familymentioning
confidence: 99%
“…2 In some cases, I observed that families did get tested when there was suspicion because of infection, especially after a death in the family. As I show in another article, one woman in Nazimabad (Karachi) had gotten herself tested when her husband died of typhoid and was being treated with suspicion by her neighbours (Khan 2020). Recent literature has made contributions about the reliability of knowledge about COVID-19 symptoms and prevention in low-income settings (Austrian et al 2020;Lau et al 2020).…”
Section: Imagining the Disease-free Familymentioning
confidence: 99%
“…Di negara-negara lain juga dilakukan penelitian dengan topik yang mirip seperti di Pakistan, Brazil, dan Australia. Berdasarkan studi Khan (2020) di Karachi, Pakistan diperoleh pemahaman bahwa walaupun banyak usaha yang telah dilakukan untuk meminimalisasi adanya kontak atau hubungan selama pandemi, masyarakat akan kembali mencari jalan lain. Daripada fokus pada hal tersebut, lebih baik memikirkan bagaimana memberikan pengetahuan medis kepada masyarakat sehingga mereka dapat menjaga dirinya sendiri dan orang lain di sekitarnya tanpa adanya rasa tertekan untuk melakukannya.…”
Section: Studi Pustakaunclassified